Right to development in the African human rights system - Kamga, Serges Djoyou (Serges Alain Djoyou Kamga) (Abingdon, Oxon ; New York, NY : Routledge, 2018)
The right to development (RTD) seeks to address global inequities hidden in world politics and global institutions through the game of influences played by powerful actors. The negative impacts of the Atlantic slave trade, colonialism, and the subjugation of Africa through globalisation and its institutions are key factors that have caused Africa and African people claiming their RTD. This book examines how the African continent protects the right to development, examining the nature of the RTD and controversies surrounding it and how it is implemented. The book then goes onto explore the RTD at the regional level including through the jurisprudence of the African Commission and the African Court on Human Rights, at the sub-regional level including in sub-regional courts and tribunals, at the national levels through case studies and through the African Union governance institutions. Through this examination, the author unveils what are the prospects and challenges to the realisation of the RTD in Africa.--
Introduction -- Unpacking the right to development -- The implementation of the right to development -- The right to development in the African human rights architecture : its reception at the regional, sub-regional and national levels -- The African Commission, the African Court on Human Rights and the realisation of the right to development -- The African Union governance institutions and the right to development -- The way forward for the realisation of the right to development in Africa.
Includes bibliographical references and index.
Keywords: Human rights; Right to development -- Legal status, laws, etc. -- Africa; Right to development -- Government policy -- Africa; Human rights -- Africa -- 21st century; Right to development; Africa